2008
DOI: 10.1002/elps.200700479
|View full text |Cite
|
Sign up to set email alerts
|

Integrated isotachophoretic stacking and gel electrophoresis on a plastic substrate and variations in detection dynamic range

Abstract: In this study, we demonstrated an integrated ITP-gel electrophoresis (GE) device on a plastic substrate, in which 50 nL of samples could be hydrodynamically or electrokinetically injected and enriched by ITP into narrow bands and then subsequently introduced into a homogeneous GE channel for separation and detection. This microchip design rendered a simple introduction scheme for creating sandwiched stacking buffer system and flexibilities in choosing separation and stacking buffers independently. We used gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…a diffuse boundary between the LE and the TE zones). This type of focusing is common in biological applications such as immunoassays and DNA or RNA separations, where sample concentrations are inherently low [34,35].…”
Section: Sample Preconcentration In Peak Mode Itpmentioning
confidence: 99%
“…a diffuse boundary between the LE and the TE zones). This type of focusing is common in biological applications such as immunoassays and DNA or RNA separations, where sample concentrations are inherently low [34,35].…”
Section: Sample Preconcentration In Peak Mode Itpmentioning
confidence: 99%
“…3 Note that ITP is not only used for small ions but has also proven useful for the analysis of nanometer sized objects. For example, it was used as a preconcentration technique for RNA and proteins in context with gel electrophoresis, 4 for purification of nucleic acids from whole blood samples, 5 or for the study of plasma lipoproteins. 6,7 Furthermore, ITP can also be combined with micellar electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45] On the other hand, a multi T-channel chip is used to inject L, sample and T solutions successively in the ITP and tITP analysis. In the recent years, α-fetoproteins, 46 DNA ladder, 47,48 and PCR products 49 are well concentrated and resolved by employing the multi T-channel chips. As a very unique approach, Bottenus et al have reported the application of a microchip with two reductions in the cross-sectional area along the axial direction of the channel to the ITP preconcentration of the biomarker cardiac troponin I and a fluorescent protein R-phycoerythrin.…”
Section: ·3 Isotachophoresis (Itp)mentioning
confidence: 99%